THE ROLE OF ARTIFICIAL INTELLIGENCE IN COMPUTER SCIENCE - Abdugafurova Zarifa Sattarovna (Ecominds Press, 2025)
This article explores the role of Artificial Intelligence (AI) in the field of Computer Science. It highlights the key areas where AI is making significant contributions, such as data analysis, machine learning, robotics, and software development. The paper also examines how AI is transforming problem-solving methods, optimizing algorithms, and enabling computers to perform tasks that typically require human intelligence. The aim is to demonstrate how AI technologies are shaping the future of Computer Science and to provide insights into current trends, challenges, and potential opportunities in this rapidly evolving domain.
Keywords: Artificial Intelligence, Computer Science, Machine Learning, Data Analysis, Robotics, Algorithms, Automation, Software Development, Neural Networks, Intelligent Systems.